First global molecular phylogeny and biogeographical analysis of two arachnid orders (Schizomida and Uropygi) supports a tropical Pangean origin and mid‐Cretaceous diversification. (20th August 2017) - Clouse, Ronald M.; Branstetter, Michael G.; Buenavente, Perry; Crowley, Louise M.; Czekanski‐Moir, Jesse; General, David Emmanuel M.; Giribet, Gonzalo; Harvey, Mark S.; Janies, Daniel A.; Mohagan, Alma B.; Mohagan, Dave P.; Sharma, Prashant P.; et al.
Abstract: Aim: We sought to illuminate the history of the arachnid orders Schizomida and Uropygi, neither of which have previously been subjected to global molecular phylogenetic and biogeographical analyses. Location: Specimens used in this study were collected in all major tropical and subtropical areas where they are presently found, including the Americas, Africa, Australia and the Indo‐Pacific region. Methods: From field‐collected specimens, we sequenced two nuclear and two mitochondrial markers, combined these with publicly available data, and conducted multi‐gene phylogenetic analyses on 240 Schizomida, 24 Uropygi and 12 other arachnid outgroups. Schizomid specimens included one specimen from the small family Protoschizomidae; other schizomid specimens were in Hubbardiidae, subfamily Hubbardiinae, which holds 289 of the order's 305 named species. We inferred ancestral areas using the Dispersal‐Extinction‐Cladogenesis model of range evolution, and we used fossil calibrations to estimate divergence times. Results: We recovered monophyletic Schizomida and Uropygi as each other's sister group, forming the clade Thelyphonida, and terminals from the New World were usually positioned as the earliest diverging lineages. The ancestral area for schizomids reconstructed unambiguously to the region comprised of Mexico, Southern California and Florida (the xeric New World subtropics). Optimal trees suggested a single colonization of the Indo‐Pacific in both orders, although this did not receive bootstrap support. Molecular dating gave an Upper Carboniferous origin for each order, and a mid‐Cretaceous expansion of Schizomida, including the origin and initial diversification of those in the Indo‐Pacific. Main conclusions: Ancestral area reconstructions, molecular dating and fossil evidence all support an Upper Carboniferous, tropical Pangean origin for Thelyphonida, Schizomida and perhaps Uropygi. Much of this region became unsuitable habitat for these arachnids during the breakup of Pangea, but they persisted in the area that is now Meso‐ and South America. From there they then expanded to the Indo‐Pacific, where schizomids today display an idiosyncratic combination of microendemism and long‐range dispersal.